Asymmetric Return Transmission from Commodity Markets to Equity Sectors: Evidence on Positive and Negative Shock Differentials - Geste, Naude Shamma (European Scientific Journal, ESJ, 2026)
This paper investigates whether positive and negative commodity return shocks generate different mean return responses in equity sectors, the asymmetric return transmission hypothesis. Using daily data from January 2010 to March 2025 for four commodity futures (crude oil, gold, copper, natural gas) and five U.S. equity sector ETFs (energy, materials, financials, industrials, technology), we implement the Hatemi-J (2012) positive-negative shock decomposition within a 13-variable Vector Autoregression estimated at seven lags (VAR(7)), and test the equality of positive and negative shock transmission coefficients via Wald tests. This paper models mean return co-movement exclusively; conditional volatility dynamics are not estimated. The principal finding is that gold asymmetry is the only statistically robust result in the data: the null hypothesis of equal positive and negative gold shock transmission is rejected at the 1% significance level for all five equity sectors, with Wald statistics ranging from 12.75 to 20.48. Positive gold shocks generate positive equity returns (β⁺ = +0.086 to +0.126) while negative gold shocks generate negative returns (β⁻ = -0.061 to -0.096), a pattern consistent with safe-haven rotation dynamics in which gold rallies accompany broad risk-on equity positioning and gold crashes accompany risk-off selling. By contrast, oil asymmetry — while directionally present in the coefficient estimates — is not statistically distinguishable from sampling variation at the 5% level in any sector. Copper asymmetry is statistically significant only for the Technology sector (Wald = 15.80, p < 0.001). Sub-period analysis reveals that oil-energy transmission exhibits sign reversals during COVID-19 and the Ukraine war, though estimates based on 231-251 observations are treated as indicative rather than definitive. A dynamic portfolio strategy based on rolling asymmetry estimates achieves a Sharpe ratio of 0.619 and a maximum drawdown of -40.6%, compared to 0.643 and -41.9% for a static commodity-equity blend. The strategy underperforms the static blend on risk-adjusted return but provides modest drawdown protection; sensitivity analysis across signal thresholds and window specifications confirms the drawdown benefit is consistent, while Sharpe ratio improvements require higher thresholds than the baseline specification.